The Relationship Between Screen Time And Grade Point Average Among Medical Students At Prima Indonesia University - Irza Haicha Pratama; Alvin Abrar Harahap; jesslyn vanesa Lui (CV. Inara, 2026)
The use of electronic devices among college students is on the rise, whether for academic or non-academic activities. Screen time encompasses various activities, such as studying, using social media, playing games, and watching videos. The purpose of this study is to determine the relationship between the duration of screen time spent on various activities and students’ GPA. This study was conducted using a quantitative design with a correlational approach, involving 220 students from the 2nd, 4th, and 6th semesters as the research sample, selected using stratified random sampling. The data were obtained throught a questionnaire and analyzed using Spearman’s rank correlation test. The results indicate that total screen time and time spent watching videos are not significantly associated with GPA (P > 0.05). In contrast, social media use showed a negative association with GPA (r = -0.196; p = 0.004), and gaming was negatively associated with GPA (r = -0.221; p = 0.001). Meanwhile, the use of electronic devices for studying was positively associated with GPA (r = 0.436; p < 0.001). This study concludes that the relationship between screen time and GPA is more strongly influenced by the type of screen-based activity rather than the overall duration of device use.